Formulation Lotion of Arabica Coffee (Coffea arabica L.) Fruit Peel Extract and Stability Test: Formulasi Lotion Ekstrak Kulit Buah Kopi Arabika (Coffea arabica L.) dan Uji Stabilitasnya - Putri, Mega Karina; Miranti , Gabriela Alitania; Dellima, Beta Ria Erika Marita (Jurnal Riseta Naturafarm, 2025)
Coffee fruit peel contains several secondary metabolite compounds whith have antioxidant activity as antiaging skin, so it can be formulated into a cosmetic preparation. Arabica coffee fruit peel is formulated into a lotion preparation with an extract concentration of 1% and various TEA concentrations (2%, 3%, and 4%). This research to determine the effecf of variations in TEA concentration on the physical properties and physical stability of lation preparations. Type of experimental research,namely measuring the effect of variations in TEA concentration in lotion preparations in the physical properties and physical stability of the roomtemperature methods measured during 28 days of storage which was tested on days 0, 7, 14, 21 and 28 including organoleptic, homogeneity, pH, spreadability,adhesion and emulsion type. The results showed that the Arabica coffee fruit peel extractlotion with varying concentrations of TEA as an emulsifier met the physical properties requirements. The stability of the room temperature methods affects the lotion preparations during the 28 days storage period, there by influencing changes in the characteristics of the preparation. Based on the results of statistical tests with a dependent T test, it was stated that lotion F2 with TEA 3% was the most stable formulation.